BENTUK KETERLIBATAN ORANG TUA PADA ANAK TK YANG BERPRESTASI MELUKIS - Ian Santikko; Lely Ika Mariyati (Fakultas Psikologi Universitas Hang Tuah, 2019)
This studied aimed to described the form of parental involvement in kindergarten who have achievement in drawing. Parental involvement can be seen from the activities of (1) parenting, (2) communicating, (3) volunteering, (4) learning at home, (5) decision making, (6) collaborating with the community. This research method used qualitative research with a phenomenological approach. Six respondents were chosen by using purposive sampling technique. Data collection was carried out using interviews and field notes conducted on six parents of students who have achievement in drawing. The results showed that parents who did not work could involve themselves more real to support their children's achievements.